Multivariate Base Rates of Low Scores on Tests of Executive Functions in a Multi-Country Latin American Sample. Issue 1 (2nd January 2021) - Rivera, Diego; Mascialino, Guido; Brooks, Brian L; Olabarrieta-Landa, Laiene; Longoni, Melina; Galarza-Del-Angel, Javier; Arango-Lasprilla, Juan Carlos
ABSTRACT: The objective of the study was to determine the prevalence of low scores in a diverse Latin American population for two neuropsychological commonly used tests to evaluate executive functions and to compare the number of low scores obtained using normative data from a Spanish-speaking population from Latin America versus an English-speaking population from U.S.A. Healthy adults (N = 5402) were administered the Modiﬁed Wisconsin Card Sorting Test and Stroop Color-Word. Low scores on measures of executive functioning are common. Clinicians working with Spanish-speaking adults should take into account the higher probability of low scores on these measures to reduce false-positive diagnoses of cognitive deficits in an individual.